Topical concentrated epinephrine (1:1000) does not cause acute cardiovascular changes during endoscopic sinus surgery. Issue 2 (18th September 2015) - Gunaratne, Dakshika A.; Barham, Henry P.; Christensen, Jenna M.; Bhatia, Daman D.S.; Stamm, Aldo C.; Harvey, Richard J.
Abstract : Background: Topical epinephrine is used in endoscopic sinonasal surgery for local vasoconstriction. Potential for cardiovascular complications remains a concern for some due to the possibility of systemic absorption. Topical vs injected epinephrine was examined in a prospective analysis of perioperative cardiovascular effects, and in an audit of cardiovascular complications during endoscopic sinonasal surgery. Methods: A prospective cohort study of patients undergoing endoscopic sinonasal surgery was performed. Topical (1:1000) and injected (1:100, 000) epinephrine were assessed. Cardiovascular outcomes of heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and electrocardiogram (ECG) changes were examined at baseline and minutely post–topical application (to 10 minutes) and postinjection (to 5 minutes). A retrospective assessment of cardiovascular events associated with a standardized regimen of topical (1:2000) and injected (1:100, 000) epinephrine was performed. Results: Nineteen patents were assessed (43.42 ± 15.90 years, 47.4% female) in the prospective analysis. Post–topical epinephrine, no significant changes occurred in any cardiovascular parameter. However, following injected epinephrine, changes in HR (59.53 vs 64.11 bpm, p < 0.001), SBP (96.16 vs 102.95 mmHg, p = 0.015), DBP (56.53 vs 60.74 mmHg, p = 0.019), and MAP (69.74 vs 74.81 mmHg, p = 0.002) occurred. On repeated‐measures analysis of variance (ANOVA) all parameters were significantly affected by injection. No ECG abnormalities were seen in either topical or injection phases. The retrospective analysis of 1260 cases identified 2 cases of cardiovascular complications (0.16%), both relating to injected epinephrine. Conclusion: Combination topical (1:1000 to 1:2000) and injectable (1:100, 000) epinephrine is safe for use in endoscopic sinonasal surgery. Injection resulted in the cardiovascular changes and accounted for the cardiovascular events reported.